2020
DOI: 10.1002/adfm.202000477
|View full text |Cite
|
Sign up to set email alerts
|

A Battery‐ and Leadless Heart‐Worn Pacemaker Strategy

Abstract: Over the past half‐century, cardiac pacing technology has adhered to one basic system. However, many pacemaker‐related complications are related to this system, particularly in terms of the power supply and leads. Here, for the first time a heart‐worn pacemaker strategy is presented, which allows batteryless powering and leadless pacing. The batteryless feature is attained via heart‐extrusion energy scavenging through a micromachined piezoelectric thick film transducer. A record in vivo output current of 30 µA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…[152] Compared to TENG devices, advanced piezoelectric materials with excellent electromechanical coupling property allowed for significantly boosted power. [153][154][155] A (72%)Pb(Mg 1/3 Nb 2/3 )O 3 -(28%)-PbTiO 3 (PMN-PT) with exceptional e 33 up to 18.03 C m -2 was exploited for building a bow-shaped PENG. The PMN-PT layer (50 µm) was sandwiched between a thin metal sheet and polymer layers to achieve desired flexibility.…”
Section: Wearable and Implantable Pacemakersmentioning
confidence: 99%
See 1 more Smart Citation
“…[152] Compared to TENG devices, advanced piezoelectric materials with excellent electromechanical coupling property allowed for significantly boosted power. [153][154][155] A (72%)Pb(Mg 1/3 Nb 2/3 )O 3 -(28%)-PbTiO 3 (PMN-PT) with exceptional e 33 up to 18.03 C m -2 was exploited for building a bow-shaped PENG. The PMN-PT layer (50 µm) was sandwiched between a thin metal sheet and polymer layers to achieve desired flexibility.…”
Section: Wearable and Implantable Pacemakersmentioning
confidence: 99%
“…Reproduced with permission. [ 155 ] Copyright 2020, Wiley‐VCH. c) Direct heart stimulation by a TENG performed under in vitro condition: i) Schematics of the PMN‐PT‐based PENG for direct pacemaking.…”
Section: Wie Applicationsmentioning
confidence: 99%
“…An important consideration in this area are the regulations around powering of medical devices and in particular, safety limits which are often established by national regulators. Examples of studies which give consideration to power include: design and testing of a far-field based radio frequency (RF) powering system for implantable devices where wireless power transfer was shown as feasible using a frequency of 403 Hz at a working distance of 17 cm; the development of an algorithm to ensure optimum power consumption and effective recharging for a network of body area sensors [47]; and finally, a study which elegantly shows development of a battery- and lead-less pacemaker where the energy harvested from contraction and relaxation of heart muscle is used to harvest the electrical energy necessary to drive a commercial pacemaker circuit [48]. To realize long-term implantation and therefore devices which can give insight into wild animal behaviour, the question of power supply and power budget is critical.…”
Section: Developments In Microsystems Engineering and Implantable Devmentioning
confidence: 99%
“…The PENG is fixed on the lead of the pacemaker to harvest energy from the lead's motion caused by heartbeats. Zhiran Yi et al proposed a self-powered leadless cardiac pacemaker [96] [85], as shown in Figure 9e. A biodegradable PENG scaffold driven by ultrasound is adapted as an electrical stimulator to promote bone regeneration.…”
Section: Self-powered Implantable Systems Based On Pengmentioning
confidence: 99%